2021
DOI: 10.1590/1982-0224-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics insights in two pelagic big-game fishes in the Atlantic, the tarpon, Megalops atlanticus (Elopiformes: Megalopidae), and the sailfish, Istiophorus platypterus (Istiophoriformes: Istiophoridae)

Abstract: Some pelagic and usually large sized fishes are preferential targets for sport and commercial fishing. Despite their economic importance, cytogenetic data on their evolutionary processes and management are very deficient, especially due to logistical difficulties. Here, information for two of such charismatic species, the tarpon, Megalops atlanticus (Elopiformes: Megalopidae), and the sailfish, Istiophorus platypterus (Istiophoriformes: Istiophoridae), both with a wide Atlantic distribution, were provided. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Integrative cytogenetic approaches in marine fish groups have indicated that specific biological aspects and historical contingency can act together as causal effects of chromosomal changes [ [1] , [2] , [3] ]. Marine fishes display contrasting karyotype evolution patterns, which can vary from high dynamic rates to stasis, a process in which chromosomal change rates are absent or slow, allowing chromosomal patterns to persist for long periods of time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Integrative cytogenetic approaches in marine fish groups have indicated that specific biological aspects and historical contingency can act together as causal effects of chromosomal changes [ [1] , [2] , [3] ]. Marine fishes display contrasting karyotype evolution patterns, which can vary from high dynamic rates to stasis, a process in which chromosomal change rates are absent or slow, allowing chromosomal patterns to persist for long periods of time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%